Typical Mri Findings of Ramsay Hunt Syndrome - Muñoz, Andrés Felipe Díaz; Ibrahim, Talel Muhieddine; Ortiz, Chiara Theresa Norato; Chávez, Ángel Fabián Leon; Amaya, Geinni Paola Barrera; Galvis, Maria Carolina Causil; Pacheco, Marlon Eduardo Freite; Herrera, Miguel Angel Iglesias (Jour Med Resh and Health Sci, 2022)
Ramsay Hunt syndrome (SRH) is characterized by its appearance in the reactivation of the Varicella Zoster virus (VZV) infection causing affections in the geniculate ganglion, more specifically in the VII pair, the prevalent age is over 60 years, causing edema, nerve compression and demyelination. This syndrome is generally diagnosed with the patient's clinic where the present history and physical examination play an important role, however, imaging studies are also used mainly in atypical forms, such as contrast-enhanced magnetic resonance imaging (MRI) of the head and neck, which allows a better visualization of compromised structures such as the brain, the base of the skull, the thyroid region and a better contrast uptake of the facial nerve and the geniculate ganglion, thus allowing the assessment of the level of compromise and existing condition